MicroRNA-497 Reduction and Increase of Its Family Member MicroRNA-424 Lead to Dysregulation of Multiple Inflammation Related Genes in Synovial Fibroblasts With Rheumatoid Arthritis - Wang, Si; Xu, Jing; Guo, Yuanxu; Cai, Yongsong; Ren, Xiaoyu; Zhu, Wenhua; Geng, Manman; Meng, Liesu; Jiang, Congshan; Lu, Shemin (Frontiers in Immunology, 2021)
Objectives: Mounting evidence has demonstrated that microRNAs (miRNAs) participate in rheumatoid arthritis (RA). The role of highly conserved miR-15/107 family in RA has not been clarified yet, and hence investigated in this study. Methods: Reverse transcription-quantitative polymerase chain reaction (RT-qPCR) was used to evaluate the expression of miRNAs and genes. Cell counting kit 8 (CCK-8) and FACS were used to detect proliferation and apoptosis. Protein expression was detected by using Western blotting. mRNA deep sequencing and cytokine antibody array were used to analyze differentially expressed genes, signaling pathways and cytokines. Results: The expression of miR-15a, miR-103, miR-497, and miR-646 was found decreased, while miR-424 increased in RA patients. MiR-424 and miR-497 were further investigated and the results showed that they could regulate the expression of multiple genes in rheumatoid arthritis synovial fibroblast (RASF) and affect signaling pathways. At the protein level, miR-497 mimic altered all the selected inflammation-related genes while miR-424 inhibitor only affected part of genes. MiR-497 mimic, rather than miR-424 inhibitor, had significant effects on proliferation and apoptosis of RASF. DICER1 was found to positively regulate the expression of miR-424 and miR-497, while DICER1 was also negatively regulated by miR-424. The increase of miR-424 could reduce miR-497 expression, thus forming a loop, which facilitated explaining the dysregulated miR-424 and miR-497 in RA. Conclusion: The miR-424 and miR-497 of miR-15/107 family affect cell proliferation and apoptosis in RA, and the proposed miR-424-DICER1-miR-497 feedback loop provides a novel insight into regulating miRNA expression and a candidate target for controlling RA.